Arab criminology - Ouassini, Nabil; Ouassini, Anwar (Abingdon, Oxon ; New York, NY : Routledge, 2023)
"The objective of Arab Criminology is to establish a criminological sub-field called 'Arab Criminology.' Presenting compelling arguments and examples that support the establishment of this sub-field, Arab Criminology will be of great interest to Criminology, Criminal Justice, Legal Studies, and Middle Eastern/North African studies scholars, particularly those working on Southern Criminology, Comparative Criminology, International Criminal Justice Systems, and Arab studies"--
Why Arab Criminology? -- The Islamic Legal Tradition -- Historical, Political and Cultural Commonalities -- Arab Criminology at the Intersection of Race and Gender -- Transnational Crime in the Arab World -- Moving Forward.
OCLC-licensed vendor bibliographic record.
Keywords: Criminology -- Arab countries; LAW / Criminal Law / General; SOCIAL SCIENCE / Islamic Studies